Ostracod biostratigraphy in the Lower Cretaceous of the Iberian chain (eastern Spain) - Schudack, U.; Schudack, M. (Journal of Iberian Geology, 2009)
Lower Cretaceous ostracod associations (marine and nonmarine) have been studied from 34 sections of the Iberian chain or, geologically spoken, the Iberian basin (eastern Spain), in order to contribute to the chronostratigraphic correlation of the various predominantly nonmarine lithostratigraphic units in the Cameros, Maestrazgo, and South Iberian sub-basins (and the Central Iberian high in between). We have combined 87 ostracod species from 22 genera to 11 associations, each typical for certain stratigraphic levels (mostly stages) and ecologies. Nonmarine associations (dominated by the genera Cypridea and Theriosynoecum) prevailed from the Berriasian to the Barremian interval, whereas marine-brackish associations (much more diverse on the generic level) prevailed during the Aptian and Albian, and to a lesser extent during the Berriasian and Barremian. In most cases, our new ostracod data are consistent with previous correlative charts, as based upon other biostratigraphic data, mainly from charophytes, but also from few marine fossils in marine intercalations, and on depositional sequence stratigraphy. But in a few cases, our results are more or less different from those of established charts, namely in the eastern Cameros sub-basin (the Urbión group considered Late Berriasian in age instead of Valanginian-Barremian, and the Enciso group considered Late Valanginian-Barremian instead of Late Barremian-Aptian), in the northeastern Maestrazgo sub-basin (the Polacos Formation considered Late Berriasian-Early Hauterivian instead of Late Berriasian only), and in the uppermost part of the Lower Cretaceous in the South Iberian sub-basin (the Contreras and El Caroig Formations considered Albian instead of Aptian). Finally, we evaluate the usability of ostracod biostratigraphy in the Lower Cretaceous of eastern Spain and conclude that, if treated with great care especially under consideration of the biogeography and reproduction/dispersal strategies of the various groups, it should be given priority over pure lithostratigraphic correlations in conflicting cases.